2018
DOI: 10.1371/journal.pone.0201402
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic kyphoplasty: A novel drug delivery system for the spinal column

Abstract: Vertebral compression fractures (VCFs) caused by metastatic malignancies or osteoporosis are devastating injuries with debilitating outcomes for patients. Minimally invasive kyphoplasty is a common procedure used for symptomatic amelioration. However, it fails in treating the underlying etiologies of VCFs. Use of systemic therapy is limited due to low perfusion to the spinal column and systemic toxicity. Localized delivery of drugs to the vertebral column can provide a promising alternative approach. A porcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A porcine kyphoplasty model was reported to show that a magnetic bone cement injected to manage vertebral compression fractures (VCFs) was able to localise systemically injected MNPs at the vertebral body where the cement was injected [ 44 ]. Therefore, it was proposed that this method could be used as an effective targeted drug delivery system for the treatment of osteoporosis induced VCFs [ 44 ].…”
Section: Magnetic Nanoparticles and Bone Tissue Engineeringmentioning
confidence: 99%
“…A porcine kyphoplasty model was reported to show that a magnetic bone cement injected to manage vertebral compression fractures (VCFs) was able to localise systemically injected MNPs at the vertebral body where the cement was injected [ 44 ]. Therefore, it was proposed that this method could be used as an effective targeted drug delivery system for the treatment of osteoporosis induced VCFs [ 44 ].…”
Section: Magnetic Nanoparticles and Bone Tissue Engineeringmentioning
confidence: 99%
“…In recent years, people have been working on finding the best drug delivery system to reduce the adverse effects and toxicity of drugs, reduce the loss of drug efficacy, and improve the therapeutic effect (Jung et al, 2018 ; Lugert et al, 2019 ; Sun et al, 2019 ; Vangijzegem et al, 2019 ). Studies found that iron oxide nanoparticles can be used as a means of delivery, which can effectively carry drug molecules under the action of an external magnetic field and target specific parts of the body (Denyer et al, 2018 ). Suspension of drug molecules on magnetic carriers or dispersion on magnetic nanoparticles is a simple and direct magnetic targeted drug delivery route (Denyer et al, 2018 ).…”
Section: Preparation Of Magnetic Nanomaterialsmentioning
confidence: 99%
“…Studies found that iron oxide nanoparticles can be used as a means of delivery, which can effectively carry drug molecules under the action of an external magnetic field and target specific parts of the body (Denyer et al, 2018 ). Suspension of drug molecules on magnetic carriers or dispersion on magnetic nanoparticles is a simple and direct magnetic targeted drug delivery route (Denyer et al, 2018 ). Recent studies have used solvent evaporation and lyophilization to prepare degradable polylactic acid-glycolic acid copolymer capsaicin-coated magnetic nanoparticles (Xia et al, 2018 ).…”
Section: Preparation Of Magnetic Nanomaterialsmentioning
confidence: 99%
“…235 Polymethylmethacrylate cement containing magnets injected into porcine thoracic vertebrae to mimic kyphoplasty attracted systemically administered magnetic nanoparticles. 236 Lumber posterolateral spinal fusion is modeled in large and small animals, among which the rodent and lapin are commonly used to evaluate de novo bone formation and remodeling in a non-instrumented model (Figure 4). [237][238][239][240] Bilateral decortication of the L4-L5 or L5-L6 transverse processes, with or without decortication of the spinous processes and lamina, produces stable fracture beds to which materials are applied topically.…”
Section: Vertebraementioning
confidence: 99%
“…As with all bones, there are important anatomical differences between human and animal vertebrae, however, the immature domestic porcine (55–65 kg) vertebral macrostructure resembles the human in pedicle dimensions, 234 vertebral body height, and end‐plate and spinal canal shape 235 . Polymethylmethacrylate cement containing magnets injected into porcine thoracic vertebrae to mimic kyphoplasty attracted systemically administered magnetic nanoparticles 236 . Lumber posterolateral spinal fusion is modeled in large and small animals, among which the rodent and lapin are commonly used to evaluate de novo bone formation and remodeling in a non‐instrumented model (Figure 4).…”
Section: Models Of Bone Regenerationmentioning
confidence: 99%